Demografi dan Komorbid dengan Kejadian Tuberkulosis Resisten Obat (TB RO) - Anisah Anisah; Dyah Wulan Sumekar; Endang Budiarti (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: TB RO cases in Lampung Province always increase from year to year with a total of 87 cases until 2020. Objective: This study aims to determine the relationship between demographics and comorbidities with the incidence of TB RO. Methods: This study is an observational analytic study, with a case-control design. The total population in this study amounted to 925 people. The number of samples was 51 people consisting of 17 cases and 34 controls or with a ratio of 1:2. The dependent variable in this study was the incidence of TB RO while the independent variables in this study were demographics which included age, gender, education, occupation, and income as well as comorbidities. The data collection tool in this study used Medical Record (RM) data at the South Lampung District Health Center. The analysis used univariate using percentage and bivariate analysis using chi-square test. Results: This study found that there was no relationship between age, gender, education, occupation, and income with the incidence of TB RO in the South Lampung Regency, while the comorbid DM variable was associated with the incidence of TB RO. Conclusion: there is a significant relationship between DM comorbid variables and the incidence of TB RO. Suggestion: suggestions that can be given to patients with drug-resistant tuberculosis are to remain obedient in consuming drugs regularly with a schedule that has been set by health workers.